A review on ethnobotany, phytochemistry and pharmacology of plant genus Caralluma R. Br. (30th April 2014) - Adnan, Muhammad; Jan, Saleem; Mussarat, Sakina; Tariq, Akash; Begum, Shaheen; Afroz, Anila; Shinwari, Zabta Khan
Abstract: Objectives: C aralluma is a xerophytic genus used as traditional medicine for the treatment of diabetes, inflammation, leprosy, obesity and rheumatism. Objectives of this review are to establish a relationship between traditional uses and scientific studies by critically evaluating the available fragmented literature on ethnobotany, pharmacology, phytochemistry and toxicology of genus C aralluma . Key findings: Ethnomedical uses of C aralluma have been recorded from various countries such as China, India, Iran and Pakistan for six major classes of diseases including diabetes and gastrointestinal disorders. This review indicated the efficacy of genus C aralluma in several in vitro and in vivo pharmacological properties such as antimicrobial, antioxidant and anticancer activity. These bioactivity might be due to the presence of certain classes of compounds in genus C aralluma including pregnane glycosides, flavonoid glycosides and flavones. Summary: Traditional uses and scientific evaluation of C aralluma indicates that it is one of the most widely used genus in some parts of the world. Further studies on the structural activity relationship of some of the isolated compound may improve their biological potency as well as scientific exploitation of traditional uses of the genus.